Using photovoice to facilitate the report of emotions in an interview setting: An experimental study - Studer, Selina; Kleinstäuber, Maria; Weise, Cornelia (PLoS ONE, 2025)
Background Finding words to describe emotional experiences can be challenging. Photovoice (PV) represents a possible way of facilitating the report of emotions. In the PV approach, people take pictures that they feel are related to a certain topic. Afterwards, they are invited to talk about this topic based on the pictures. There is a lack of experimental studies investigating the effectiveness of PV to aid in emotional processing in comparison to other methods. Methods Sixty-five participants were randomly assigned to one of three groups (mean age: 28.23 years [SD = 9.23], 76% female). The photovoice-group received the task to take pictures that reflect future worries about something in the future. Participants in the active control group, the writing group, were instructed to write down their future worries. The control group did not receive an assignment. In a subsequent semi-structured interview, all participants were invited to talk about their future worries. The interviews were audio-recorded and later transcribed. The number of emotion words was counted during the transcriptions. After the interview, participants completed an online self-report questionnaire addressing a range of variables such as the participants’ emotional state and their perceived difficulty identifying emotions. Results Contrary to our hypotheses, one-way ANOVAs revealed no differences in any of the self-report measures between the three study groups (all p values > 0.14). Planned contrasts regarding the transcribed interviews revealed, however, that the PV-group reported more negative emotion words compared to the two other groups t(62) = 2.79, p = .007, and also compared to the WG only, t(62) = 2.48, p = .016. Conclusions and implications The discrepancy between self-report regarding emotionality in the questionnaires and emotion words observed during the interviews is notable. PV increased the observational emotion report even in a sample with high emotional awareness. Future research should examine if PV can facilitate emotion reporting in a clinical sample.
CRIS-Team Scopus Importer:2025-05-16